Foveal changes in aquaporin‐4 antibody seropositive neuromyelitis optica spectrum disorder are independent of optic neuritis and not overtly progressive. (23rd March 2021) - Roca‐Fernández, Adriana; Oertel, Frederike Cosima; Yeo, Tianrong; Motamedi, Seyedamirhosein; Probert, Fay; Craner, Matthew J.; Sastre‐Garriga, Jaume; Zimmermann, Hanna G.; Asseyer, Susanna; Kuchling, Joseph; Bellmann‐Strobl, Judith; Ruprecht, Klemens; et al.
Abstract: Background and purpose: Foveal changes were reported in aquaporin‐4 antibody (AQP4‐Ab) seropositive neuromyelitis optica spectrum disorder (NMOSD) patients; however, it is unclear whether they are independent of optic neuritis (ON), stem from subclinical ON or crossover from ON in fellow eyes. Fovea morphometry and a statistical classification approach were used to investigate if foveal changes in NMOSD are independent of ON and progressive. Methods: This was a retrospective longitudinal study of 27 AQP4‐IgG + NMOSD patients (49 eyes; 15 ON eyes and 34 eyes without a history of ON [NON eyes]), follow‐up median (first and third quartile) 2.32 (1.33–3.28), and 38 healthy controls (HCs) (76 eyes), follow‐up median (first and third quartile) 1.95 (1.83–2.54). The peripapillary retinal nerve fibre layer thickness and the volume of combined ganglion cell and inner plexiform layer as measures of neuroaxonal damage from ON were determined by optical coherence tomography. Nineteen foveal morphometry parameters were extracted from macular optical coherence tomography volume scans. Data were analysed using orthogonal partial least squares discriminant analysis and linear mixed effects models. Results: At baseline, foveal shape was significantly altered in ON eyes and NON eyes compared to HCs. Discriminatory analysis showed 81% accuracy distinguishing ON vs. HCs and 68% accuracy in NON vs. HCs. NON eyes were distinguished from HCs by foveal shape parameters indicating widening. Orthogonal partial least squares discriminant analysis discriminated ON vs. NON with 76% accuracy. In a follow‐up of 2.4 (20.85) years, no significant time‐dependent foveal changes were found. Conclusion: The parafoveal area is altered in AQP4‐Ab seropositive NMOSD patients suggesting independent neuroaxonal damage from subclinical ON. Longer follow‐ups are needed to confirm the stability of the parafoveal structure over time. Abstract : This paper provides evidence that the fovea is wider in eyes without a history of optic neuritis (NON eyes) in patients with neuromyelitis optica spectrum disorder (NMOSD), whereas optic neuritis (ON) eyes typically presented with a flatter fovea compared to healthy controls and NON eyes. The discriminatory analysis strongly suggests that changes in NON eyes are not caused by subclinical optic neuropathy or ON. Our study supports a model in which aquaporin‐4 antibody affects antigen‐expressing glial cells in NMOSD, in this case Müller cells, without complement involvement. This has relevance for the pathological understanding of NMOSD as well as potential clinical implications.